Unlocking the Potential of Digital Payment: How Financial Habits Drive Digital Payment Adoption Among Indonesia's MSMEs - Sutrisno, Evelin; Nainggolan, Romauli (Jurnal Aplikasi Manajemen, 2025)
Financial literacy is essential for proficient financial management, impacting the utilization and enhancement of financial technology such as digital payment within Micro, Small, and Medium Enterprises (MSMEs). This study investigates the influence of financial literacy on the effectiveness of digital payment use, with financial behavior serving as a mediating variable. It also examines the moderating influence of gender in these connections to further the understanding of digital payment adoption dynamics. This study employed a quantitative methodology, utilizing Structural Equation Modeling (SEM) for data analysis. A purposive sampling strategy identified 192 MSME owners utilizing Quick Response Code Indonesian Standard (QRIS) from four Indonesian cities: Medan, Bali, Makassar, and Surabaya, reflecting diverse economic and technological environments. Data were collected using a structured questionnaire and processed with SmartPLS 4.0. The findings indicate that financial literacy substantially affects the effectiveness of QRIS use, both directly and indirectly through financial behavior. Owners of MSMEs possessing elevated financial literacy exhibit superior financial conduct, including systematic cash flow management, hence augmenting QRIS utilization. Gender is a moderating variable in the correlation between financial literacy and financial behavior, indicating disparities in financial habits among men and women. This study underscores the significance of customized financial education programs to improve financial literacy and practices among MSMEs. Optimizing QRIS adoption can improve financial transparency, operational efficiency, and competitiveness, facilitating Indonesia's shift towards a more inclusive and sustainable digital economy.